Broad threat to humanity from cumulative climate hazards intensified by greenhouse gas emissions. Issue 12 (December 2018) - Mora, Camilo; Spirandelli, Daniele; Franklin, Erik; Lynham, John; Kantar, Michael; Miles, Wendy; Smith, Charlotte; Freel, Kelle; Moy, Jade; Louis, Leo; Barba, Evan; Bettinger, Keith; et al.
Abstract The ongoing emission of greenhouse gases (GHGs) is triggering changes in many climate hazards that can impact humanity. We found traceable evidence for 467 pathways by which human health, water, food, economy, infrastructure and security have been recently impacted by climate hazards such as warming, heatwaves, precipitation, drought, floods, fires, storms, sea-level rise and changes in natural land cover and ocean chemistry. By 2100, the world's population will be exposed concurrently to the equivalent of the largest magnitude in one of these hazards if emmisions are aggressively reduced, or three if they are not, with some tropical coastal areas facing up to six simultaneous hazards. These findings highlight the fact that GHG emissions pose a broad threat to humanity by intensifying multiple hazards to which humanity is vulnerable. This Review examines the pathways through which humans are impacted by climate change and shows that by 2100 the world's population will be simultaneously exposed to at least three hazards, and in some locations as many as six, under an RCP 8.5 scenario.